The Effect of Relational Marketing on Customer Loyalty Through Satisfaction and Trust of Islamic Bank Savings Customers in Klaten City - Kusuma Herning, Belda Kumaratih; Sholahudin, Muhammad (Pusat P2M Politeknik Negeri Batam, 2024)
This study aims to analyze the effect of relational marketing on customer loyalty through satisfaction and trust in Islamic bank savings in Klaten city. This research method is quantitative. The data source of this research is primary data. The data collection method used in this research is by distributing questionnaires. The population of this study is a company that carries out business activities based on sharia principles or Islamic law. With a sample size of 132 respondents based on Malhorta's calculation. After the data is collected, it is analyzed using SmartPLS4.0 software. The results that can be revealed in this study are Relational Marketing has no significant effect on Customer Loyalty, Relational Marketing has a significant positive effect on Customer Satisfaction, Relational Marketing has a positive and significant effect on Customer Trust, Customer Satisfaction has no effect on Customer Loyalty, Customer Trust has a positive and significant effect on Customer Loyalty, Customer Satisfaction does not mediate the relationship between the effect of Relational Marketing on Customer Loyalty, Customer Trust mediates the relationship between the effect of Relational Marketing on Customer Loyalty.